Exogenous Recombinant Adiponectin Improves Survival in Experimental Abdominal Sepsis - Bülent Salman; Tonguç Utku Yılmaz; Tugan Tezcaner; Ebru Ofluoğlu Demir; Özge Tuğçe Paşaoğlu (Balkan Medical Journal, 2014)
Background: Adiponectin, which has anti-inflammatory features, is an important substance in several metabolic mechanisms.